The role of organizational fairness in the performance of the faculty at the Technical Institute Hawija - كريم خولة صدر الدين (Journal of Economics and Administrative Sciences, 2019)
This study aims to show the level of organizational fairness at Hawija Technical Institute ,from the point view of the faculty ,and the degree of their performance, and the nature of the relationship between organizational fairness and their performance. The researchers accomplish and develop a questionnaire on Likert a three - dimensional scale to de applied on a sample chosen randomly strength (50) faculty and the results were analyzed by may statistical methods in order to achieve the hypothesis of the research to be used by the Institute under study , to avoid many problems ,and to uplift the message of this teaching foundation . Recommendations are put forth in applying fairness to boost the functional performance of the faculty through fulfill their wants and need , which have.